RETRACTED: Intra-articular Injections With Either Triamcinolone Hexacetonide, Stanozolol, Hylan G-F 20, or a Platelet Concentrate Improve Clinical Signs in Police Working Dogs With Bilateral Hip Osteoarthritis - Alves, João C.; Santos, Ana; Jorge, Patrícia; Lavrador, Catarina; Carreira, L. Miguel (Frontiers in Veterinary Science, 2021)
Objectives: To compare the effect of intra-articular treatment with triamcinolone hexacetonide (TH), stanozolol, hyaluronan, and a platelet concentrate (PC) in police working dogs with bilateral hip osteoarthritis (OA). Study design: Prospective, longitudinal, double-blinded, negative controlled study. Sample population: Fifty police working dogs with naturally occurring hip OA. Methods: Animals were randomly assigned to a control group (CG, n=10), TH group (THG, n=10), PC group (PCG, n=10), stanozolol group (SG, n=10), and Hylan G-F 20 group (HG). On days 0 (T0), 8, 15, 30, 90, and 180 days post-treatment, weight-bearing distribution was evaluated. In those days, and on days 60, 120, and 150, four clinical metrology instruments were completed. Kaplan-Meier estimators were conducted and compared with the log-rank test. Cox proportional hazard regression analysis was performed to determine treatment survival. Significance was set at p<0.05. Results: Patients had a mean age of 6.5±2.4 years and bodyweight of 26.7±5.2kg. At T0, hips were classified as mild (n=35), moderate (n=10), and severe (N=5), according to the Orthopedic Foundation for Animals grading scheme. No differences were found between groups at that moment considering all assessments performed. All treatments were improved clinical signs in various OA dimensions in some groups, with a broad effect interval. PCG showed a lower range of variation while maintaining a positive result for more extended periods (p<0.01 for symmetry index and 0.01<0<0.04 in the majority of scores). Breed, age, sex, and OFA grade did not significantly influence response to treatment. Conclusions and Clinical Relevance: This is the first prospective, negative controlled, double-blinded study to compare the effect of IA treatments in dogs with hip osteoarthritis. HG and PCG recorded more significant improvements throughout the 180-day follow-up. In particular, PCG also registered a lower variation in results, seemingly the best therapeutic option. Nevertheless, improvements were still observed in THG and SG, and these treatment options can be considered, mainly when the first two treatments are not available.